A cross-sectional study on knowledge, attitude & practice towards organ & tissue donation among patient’s attendant in tertiary care hospital. (Journal of Forensic Medicine & Toxicology, 2025)
Background: Organ transplantation is one of the life-saving treatment needed for survival but the disparity in the  number of recipients and donors are expansive & unequivocal. This study aims to assess the knowledge, attitude & prac tice of organ & tissue donation among patient’s attendant in a tertiary care hospital. Material & Methods: A descriptive  cross-sectional study was conducted among patient’s attendant in tertiary care hospital. The interview was carried out  vis-à-vis using a 25 structured questionnaire and analysed using SPSS (IBM version 20, Armonk, NY, USA) Results: 100  consenting patient’s attendants were interviewed in the median age of 21-30years (43%) with a male: female sex ratio of  1:1.6. Majority of the interviewees were aware of organ transplantation however 52% did not know about donor registry.  It was also observed that 37% didn’t know about cadaveric organ donation & 76% were willing to donate organs after  death. Majority (87%) of the participants think that donating one’s organ adds meaning to one’s life yet 66% had not  pledged/signed for donating organs. It is also detected that 49% of unwillingness for organ donation is due to unawareness while 21% had their reservation due to organ mutilation. This study also reflected that 59% were of the believe that  organ donation will affect their lifestyle. Conclusion: At the end of the study, it is observed that majority of them had the  knowledge on organ donation but were unaware of its process for registering as organ donor.
Keywords: Organ transplantation; knowledge; attitude; practice; interview